(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The study’s aim is to create and test job satisfaction and body image scales, as well as to identify the relationship between them among physical training instructors at the Iraqi Police College. The researcher used the descriptive survey method, normative and correlational studies, and the research sample included (210) physical training teachers from the Iraqi Police College. In order to achieve the research objectives, job satisfaction and body image scales were constructed and prepared by following the steps and procedures for constructing and preparing psychological scales and processing their data with the statistical bag for social sciences (SPSS). The study came to several conclusions, including The higher the job satisfaction of physical training teachers, the more positive body image there is. Among the most important recommendations that the researcher intends to consider is: paying attention to the concept of body image as perceived by society in particular, due to the importance of that for physical training instructors at the Iraqi Police College.